<h3>
Step-by-step explanation:</h3>
<u>Pythagorus theorum:</u>
9² = 3² + YZ²
81 - 9 = YZ²
√72 = YZ
∴YZ= 8.48 ≈ 8.5
<u>Trigonometry:</u>
We have adjacent as 3, and hypotenuse as 9
cos X = 3/9
X= cos∧-1 (3/9) → <em>[cos inversed]</em>
∴X= 70.5°
We have opposite as 3 and hypotenuse as 9
sin Z= 3/9
Z= sin∧-1 (3/9)→<em> [sin inversed]</em>
∴Z= 19.47 ≈ 19.5
Step-by-step explanation:
By using Implicit Differentiation,
d/dx (y² + xy - x²) = d/dx (11x)
d/dx (y²) + d/dx (xy) - d/dx (x²) = 11
2y * dy/dx + x * dy/dx + y - 2x = 11
dy/dx (2y + x) = 11 + 2x - y
dy/dx = (11 + 2x - y) / (2y + x).
At the point (2, 3), we have x = 2, y = 3.
=> dy/dx = (11 + 2(2) - (3)) / (2(3) + (2))
= 12 / 8 = 1.5.
P.S. Your question is weird because (2,3) is not on the graph, let me know what is the correct question thanks!
Answer:
all i know is A and it is -1,-2
Step-by-step explanation:
It moves in a horizontal line. Its 'y value' does not change.
The answer is A! The simplified equation would be 6x-6+8 and then it simplifies to 6x+2!